Музичките карактеристики на инструменталната македонска етнопоп музика од 80-тите години на 20-тиот век - Димитријевски, Александар (Асоциация за антропология, етнология и фолклористика »Онгъл«, 2019)
The instrumental Macedonian ethnopop music is particularly interesting phenomenon because of its development and prolonged existence in conditions with persistent internal influences of the social and economic environment, but also external influences from the neighboring and distant music cultures. These influences have determined the way of the creation of this music and its final musical products. Regarding the fact that the instrumental Macedonian ethnopop music had its peak especially in the 1980ties, the subject of interest in this paper will be the musical pieces from the mentioned period. Also, a special attention will be dedicated to the creativity, in other words to the process of creation of the instrumental Macedonian ethnopop music and the reproductive process of this music. The conclusions will be based on the analysis of the music characteristics of the recorded material which forms the database of the sample of 100 music pieces.
The Music Characteristics of the Instrumental Macedonian Ethnopop Music from the 1980ties
ДВАНАДЕСЕТИ ЦАР-ШИШМАНОВИ ДНИ В САМОКОВ ТРИДЕСЕТ И ОСМИ НАУЧНИ ЧЕТЕНИЯ НА АСОЦИАЦИЯ ЗА АНТРОПОЛОГИЯ, ЕТНОЛОГИЯ И ФОЛКЛОРИСТИКА „ОНГЪЛ“
Keywords: Macedonian ethnopop music; 1980s